Economic Feasibility Analysis Based on Reservoir Storage Capacity on the Construction of the Rongkong Multipurpose Dam - Elang Timur M. Patih Ragananda; Ussy Andawayanti; Evi Nur Cahya (PT Mattawang Mediatama Solution, 2023)
The construction of Rongkong Multipurpose Dam located in North Luwu Regency, South Sulawesi aims to provide irrigation water, water supply, and increase electricity production capacity through hydropower with 6 construction sites under consideration. Economic feasibility analysis was carried out to obtain construction sites that have the best economic feasibility objectively. In this analysis, the parameters of Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit-Cost Ratio (BCR) were calculated by considering the reservoir storage capacity in each sites. The result from this analysis shows that Site Tandung 2 is the location that has the best economic feasibility with reservoir capacity of 23,400 million m3 and Benefit- Cost Ratio (BCR) of 2.490.